2015
DOI: 10.1590/2359-3997000000100
|View full text |Cite
|
Sign up to set email alerts
|

The c.63A>G polymorphism in the NKX2.5 gene is associated with thyroid hypoplasia in children with thyroid dysgenesis

Abstract: Objective: To search for genetic alteration in NKX2.5 gene in patients presenting both congenital heart disease (CHD) and TD. Subjects and methods: Individual phenotypes were carefully analyzed in 86 children with thyroid dysgenesis (TD) using thyroid function tests, scintigraphy, ultrasound and echocardiography. DNA was extracted and NKX2.5 gene coding region was amplified by polymerase chain reaction (PCR) and sequenced. Results: CHD were found in 8.1% of patients with TD. The mutation screening revealed two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…NKX2-5, also associated with cardiac malformations, was found with 3 heterozygote mutations in a single study with a cohort of 241 patients (32). In our study, seven patients (2 females and 5 males) presented congenital heart disease (CHD) associated with TD, previously described in electronic records (25).…”
Section: Genetics Findingsmentioning
confidence: 52%
See 1 more Smart Citation
“…NKX2-5, also associated with cardiac malformations, was found with 3 heterozygote mutations in a single study with a cohort of 241 patients (32). In our study, seven patients (2 females and 5 males) presented congenital heart disease (CHD) associated with TD, previously described in electronic records (25).…”
Section: Genetics Findingsmentioning
confidence: 52%
“…Along with a greater gender discrepancy, those with ectopy (p ≤ 0.05) and agenesis (p ≤ 0.001) had medians of TSH that were notably higher at the initial newborn screening and confirmatory serum TSH testing compared with hypoplasia and hemiagenesis. To the best of our knowledge we are the first researchers in Bahia to perform this type of genetic analysis for candidate thyroid embryogenesis genes PAX-8, NKX2-5, TSH-R and HES-1 in confirmed cases of permanent CH and TD (25). It should be noted that we excluded NKX2-1 and FOXE-1 from our analysis, based upon the fact that the phenotype presenting in our cohort showed no signs of Bamforth-Lazarus syndrome or neurological findings (26).…”
Section: Genetics Findingsmentioning
confidence: 99%
“…Cerqueira et al studied with thyroid dysgenesis patients and found polymorphism (c.63A>G) among the study population. This variation did not involve an amino acid alteration [16].…”
Section: Discussionmentioning
confidence: 87%
“…Cerqueira et al demonstrated a significant association of c.63A>G polymorphism with thyroid hypoplasia ( p < 0.036). The c.541G>A variant was observed in only one patient with isolated thyroid hypoplasia [ 11 ]. Long et al through targeted next-generation sequencing of thirteen causative genes in 106 Chinese patients with CH was able to detect one novel missense NKX2-5 mutation (c.416G>A in exon 2, NM_001166176) in one patient with TD (type not specified) [ 12 ].…”
Section: Discussionmentioning
confidence: 99%